KETERAMPILAN SOSIAL SISWA DI KELAS VII SMP NEGERI 8 OBA TENGAH - Oktosiyanti M.T. Abdullah (Universitas Khairun, 2018)
Social skills there needs to be a form of development by the students themselves, namely developing interests and talents through skills that grow in the students' personal approach to the learning process in schools to become students categorized in the next generation of the nation. This research is expected to provide information about how the social skills of students in Junior High School, as well as the contribution of the author to the development of educational science. To know the Social Skills of Class VII Students of SMP N 8 Oba Tengah. Based on the results of the above research, the researcher can conclude that the characteristics of students in class VII of SMP Negeri 8 Oba Tengah that have social skills are students who have communication skills, cooperative ability, firm attitude, responsibility, skills to sympathize with all friends and teachers and the communities they occupy, and involve themselves in a social gathering. So that the success of an education is not only measured by the achievement of aspects of knowledge, but more importantly from the aspects of attitude and behavior and in terms of skills as one of the subjects in basic education, it is expected to be able to prepare, foster and shape the ability of students who master the attitudes of values and social skills needed for life in the community.